Comparison of lower limb segment forces during running on artificial turf and natural grass. (May 2019) - McMurtry, Shea; Fiedler, Goeran
Introduction: Artificial turf, soon after being introduced in the 1980s, became associated with an increased injury incidence in football players. While more recent generations of artificial turf have mitigated the problem, perception of the material is still widely negative. So, the decision to play the 2015 Fe'de'ration Internationale de Football Association Women s World Cup in Canada on artificial turf was met with vocal criticism by many players. One common approach is to assess injury incidence to quantify risk differences in playing surfaces. This, however, does not account for possible confounding variables or chronic injuries. Direct measurement of ground reaction forces is difficult because conventional multicamera-based motion capture and force plate equipment are limited in its use outside of dedicated laboratories. Methods: We describe a method of generating realistic force data by using miniature load cells that are installed directly into the weight-bearing structure of the body. Results: Pilot data show a significant (p<0.01) difference in peak forces on artificial turf (272% of body weight) and natural grass (229% of body weight). Discussion: Invasive surgical procedures were avoided by installing the load cell into the prosthesis of an athlete with lower limb loss. As modern prosthetic devices allow a close approximation of able-bodied kinematics and kinetics, such prosthesis-based data are transferable to a general population.